(untitled) (Journal of Educational Sciences, 2020)
The article discusses the didactic possibilities of using “pedagogical drawing” when teaching the compulsory discipline “Electricity and magnetism” to physics students. The connection between thinking and understanding the language of physics is touched upon. The authors analyze the concept of “pedagogical drawing” in the teaching methodology of the discipline, the concept of didactic reference point, “graphic abstract”. The purpose of this article is to show the significance of the use of “teaching drawing” in the transformation of theoretical knowledge on the subject “Electricity and magnetism” in the images; students ‘ acquisition of physics skills visual-figurative thinking and the use of physical terms and symbols. The article attempts to develop a methodological method for determining the didactic reference point of «pedagogical drawing «in the teaching of the compulsory discipline «Electricity and magnetism». Teaching idea teaching guide «teaching drawing» includes steps: in the preparation of the teacher to the lesson – identifying potential opportunities didactic “teaching drawing”, during the sessions – the understanding and discussion of potential “pedagogical drawing” for students. Through physical drawing, explaining its meaning, students form both visual and imaginative thinking and scientific language, and understanding the language of physics is a component of personally significant characteristics of the future specialist. The article illustrates the simplest tasks on «pedagogical drawing» for students in the course of the compulsory discipline “Electricity and magnetism. As part of the methodological research, a survey of students was conducted to test the method of admission. It is established that students are aware of the need to use «pedagogical drawing» in teaching the discipline, understand the role of physical drawing in this issue. Key word: «pedagogical drawing», «graphic abstract», competence, visual and imaginative thinking, educational process, the language of physics, the potential of physics.